(untitled) (Caderno Espaço Feminino, 2014)
Resumo Este artigo se insere no debate de "gênero e política" ao apresentar parte de pesquisa acerca da trajetória de nove mulheres representantes do Estado do Espírito Santo no Congresso Nacional. Avalia aspectos de gênero que permeiam a representação política de mulheres, sobretudo na política brasileira, e apresenta alguns dos dilemas debatidos nesse campo de estudo. Palavras-chave: Mulheres. Trajetórias Políticas. Feminismo. Legislativo. Abstract This article takes part in the discussion of "gender and politics" by presenting the research about the history of nine women representatives of Espírito Santo in the Brazilian National Congress. It evaluates aspects of gender that permeate the political representation of women, especially in Brazilian politics, and presents some of the dilemmas discussed in this field of study. Keywords: Women. Political Trajectories. Feminism. Legislative.